Regional Economic Outlook, October 2020, Europe : Whatever It Takes: Europe's Response to COVID-19. (International Monetary Fund, 2020)
The COVID-19 pandemic has caused dramatic loss of human life and major damage to the European economy, but thanks to an exceptionally strong policy response, potentially devastating outcomes have been avoided.